Maternidad y trabajo productivo de mujeres profesionales del Centro Parroquial de Pilahuín en el año 2022. - Arroba Santiana, Ana Lucia (2023)
This paper examines women's restrictions when deciding to have children and goes beyond the limits of what is allowed to reconcile maternity leave and professional promotion. For this reason, the main objective of the research is to determine maternity as a limiting factor of productive work in professional women of the Pilahuín parish center in the year 2022. Maternity and productive work is a situation that has been addressed in recent years at the national and international level, however, the employment situation for women has not improved much in recent years. For the development of this research, it is intended to use a qualitative methodology, which will allow the analysis of the information obtained through the application of a data collection instrument, which is life histories, which will help to establish the social causes. perceived by women in the face of the set of difficulties and conflicts that their experience of maternity entails in their productive experience. Keywords: Maternity, Woman, Professional, Productive Work, Sociology of Gender